Benoît-Dominique de la Soujeole, Paternités et fraternités spirituelles, Éditions du Cerf, Paris 2021 - Nawracała, Tomasz (Poznańskie Studia Teologiczne, 2021)
Fraternity and paternity are two concepts that have appeared frequently in recent documents of the Church’s Teaching Office. They are meant to bring closer the complex structure of the relationships that exist between the individual members of the Church. Their spiritual understanding is based not on abstraction, but on the biological experience known to man. Paternity and fraternity are concepts related to family and social life, and when applied to religious space, they do not retain their universal and fundamental understanding. Fr Benoît-Dominique de la Soujeole OP’s book is a theological reflection on the understanding of the concepts of paternity and fraternity and their implications for priests and spiritual directors.